Optimization Process Parameters of Equal Angular Channel Pressing According to the Measurement Results of Microstructural Homogeneity - Bulutsuz, Asli Gunay; Yurci, Mehmet Emin; Durakbasa, Numan (UNIV FED SAO CARLOS, DEPT ENGENHARIA MATERIALS, 2018)
The aim of the present work is to discuss process parameters effect on microstructure evolution and formation mechanism of ultrafine grains. As plastic deformation technique Equal Channel Angular Pressing (ECAP) method used pure Ti G4 rods processed in order to obtain fine grained micro structure. Equal Chanel Angular Pressing technique was conducted at different processing route, process temperature, pressing velocity with an orthogonal design to critically evaluate the significance of these process parameters with their different levels. The microstructure was observed with optical and electron back scattering diffraction (EBSD) microscope. The mechanical properties were tested with tensile, hardness tests and phase is controlled with XRD analysis.
Keywords: Experimental Design; Optimization; Measurement; ECAP; Titanium; PURE TI; DEFORMATION STRUCTURES; MECHANICAL-PROPERTIES; TEMPERATURE; EXTRUSION; BEHAVIOR; CREEP; Materials Science